MACULAR DETACHMENT ASSOCIATED WITH ANOMALOUS OPTIC NERVES AND DURAL ECTASIA IN 49, XXXXY SYNDROME. Issue Volume 12:Issues 1(2018) (2018) - Hajrasouliha, Amir R.; Moss, Heather E.; Maralani, Pejman J.; Kaufman, Lawrence; Grassi, Michael A.
Abstract : Purpose: To present a case of a patient with XXXXY syndrome, anomalous optic nerves, and dural ectasia in conjunction with macular detachment. Methods: Case report. Results: A 3-year-old boy with XXXXY chromosomal abnormality presented with bilateral maculopathy. On evaluation, he was found to have anomalous optic disks with serous detachment of the left eye. Magnetic resonance imaging of the brain revealed bilateral optic nerve dural ectasia without evidence of elevated intracranial pressure. Conclusion: XXXXY syndrome, like the related condition of Klinefelter syndrome, can manifest with ocular abnormalities. In the present case, the dural ectasia may have facilitated access of cerebrospinal fluid through anomalous optic nerves, resulting in neurosensory detachment. Abstract : XXXXY syndrome, like the related condition of Klinefelter syndrome, can manifest with ocular abnormalities. In the present case, the dural ectasia may have facilitated access of cerebrospinal fl uid through anomalous optic nerves, resulting in neurosensory detachment.